Teleodontology in the Central Peruvian Jungle: Quality and Service Satisfaction - Ríos-Caro, Teresa Etelvina; León Rodríguez, Jhair Alexander; Coronel-Zubiate, Franz Tito; Ríos-Angulo, Carlos Manuel; Ríos-Caro, Marco Cesar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The research analyzes the teledentistry service applied in health services during COVID-19, studying the quality of the teledentistry service and the level of satisfaction of patients treated with this care model. A sample of 341 patients was worked on, using the SERVQUAL model. The results showed a statistically significant relationship between quality of service in teledentistry and patient satisfaction (p<0.05), where 34.9% patients perceived low quality of service and dissatisfaction, while 33.7% were pleased with the care. We conclude that, given the dental health difficulties, the population of the Peruvian central jungle is dissatisfied with the teledentistry service.